1993
DOI: 10.2165/00019053-199303050-00005
|View full text |Cite
|
Sign up to set email alerts
|

Time Preference for Health Gains Versus Health Losses

Abstract: The purpose of this research was to determine whether people devalue further health gains differently from future health losses. 108 subjects in various states of health were randomised to groups that rated their preference for a hypothetical health gain or loss of variable duration and delay, in the condition of arthritis. Direction and duration of the hypothetical future health change had an interactive effect on time preference (p less than 0.001). For the health gain, devaluation due to delay was consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 10 publications
3
43
0
1
Order By: Relevance
“…Thaler (1981) showed the underlying discount rates differ significantly for both framings. In fact, in many studies subjects have shown a preference to incur in a loss immediately rather than delaying it (Benzion, Rapoport & Yagil 1989;Loewenstein 1987;MacKeigan et al 1993;Mischel, Grusec & Masters 1969;Redelmeier & Heller 1993;Yates & Watts 1975).…”
Section: Other Anomaliesmentioning
confidence: 99%
“…Thaler (1981) showed the underlying discount rates differ significantly for both framings. In fact, in many studies subjects have shown a preference to incur in a loss immediately rather than delaying it (Benzion, Rapoport & Yagil 1989;Loewenstein 1987;MacKeigan et al 1993;Mischel, Grusec & Masters 1969;Redelmeier & Heller 1993;Yates & Watts 1975).…”
Section: Other Anomaliesmentioning
confidence: 99%
“…[Nonconstant exponential discounting has been found in stated-preference as well as revealed-preference studies, using not only monetary rewards (12,(15)(16)(17)(18)(19)(20)(21)(22) but also nonmonetary rewards (4,10,(23)(24)(25) Figure 1 compares the discount factors generated by the constant exponential function (r ) 0.10) and a generalized hyperbolic function (F ) 0.20; R ) 0.20). Given these parameter values, the hyperbolic discount function places less weight on the near future than the constant exponential discount function and greater weight on the more distant future.…”
Section: Introductionmentioning
confidence: 99%
“…This may apply to the loss scenarios as well. In the experimental or survey settings where this theory has been tested, the loss scenarios are certain and clearly defined, so that the sequence had integrity (MacKeigan et al 1993;Redelmeier and Heller 1993). In many real world scenarios, the time period during which someone has to absorb a loss created by borrowing is somewhat indeterminate.…”
Section: Conclusion: Some Future Directionsmentioning
confidence: 99%